Art continuity in religious works - Жумажанова, Ф. Т.; Коптилеуова, Д. Т. (Journal of Oriental Studies, 2018)
In the article authors discusses the ancient literary written monuments as sources of continuity of traditions in the Kazakh literature. Analysis and comprehensive description of the discussed written monuments are given.